Giving Everyone a Chance at Global Mobility (Comparative & International Education Series, 2021)
Global mobility has historically been an expensive endeavor, one that only a minority of people were fortunate enough to enjoy. Although the opportunity to travel abroad has extended to students receiving financial aid, it is still not readily feasible for students to travel for a semester, summer, or even a month abroad. Students from lower SES, frequently of a sociological minority group, and nontradditionally-aged students are often at a disadvantage for partaking in study abroad activities due to financial challenges and other responsibilities they have both in their homes (e.g., caring for a family) and at work. For example, for the student who must work while attending college, the idea of leaving their hometowns for more than one week, even if they could afford it, is not a reality. As a result, these very people are disadvantaged when it comes to developing international and cross-cultural competences. In today’s workforce, students with some international experiences are more competitive than those without (Anderson, Lawton, Rexeisen, & Hubbard, 2006; Marcotte, Desroches, & Poupart, 2007). This chapter provides some innovative solutions by introducing two unique pedagogical designs to global mobility that provide nearly every student an opportunity to gain international cross-cultural competences. The first approach is an intensive faculty-led collaborative short-term study abroad program (IFC-ST-SAP) that is covered fully by student tuition for a three-credit course. The second approach is an intensive faculty-led collaborative virtually abroad program (IFC-VAP). In the IFC-ST-SAP, faculty from two or more universities create a collaborative course project(s) that students in the participating universities work on jointly throughout a defined period of time, inclusive of an 8-10-day study abroad period. In the IFC-VAP, students never leave their home towns, but instead work with their peers in the participating universities on a series of projects. The short-term study abroad component is no longer novel (Gaia, 2015), however there is some indication that it might have only minimal impact (Lemmons, 2015; Nguyen, Jefferies, & Rojas, 2018). One remedy is to stimulate direct interaction with people in another country. Therefore, both engagements require a partnership and collaboration with faculty and students in at least one host university. They both also consist of a virtual component, which, in itself, is becoming a prominent “cultural space” that students must learn to navigate. Thus, having to study in a virtual environment, let alone a cross-cultural one, sharpens students’ resilience in preparation for a competitive work environment (Glazer, Koszusnik, & Shargo, 2012). The pedagogical designs not only appeal to the educational goal of internationalization for all students, but it also creates a tangible approach that can resonate with administrators as they revise institutional policies to make global mobility accessible to everyone. Students’ reflections on highlights and lowlights of their experiences will complement works that empirically justify the value of an IFC-ST-SAP and IFC-VAP and present a return on investment for universities.